A contribuição da universidade com o desenvolvimento sustentável no Brasil: análise da institucionalização do HIDS-Unicamp - Dibbern, Thais Aparecida (2023)
This article aims to discuss the International Hub for Sustainable Development (HIDS), integrated into the University of Campinas (Unicamp/Brazil) and to the regional context of the city of Campinas, state of São Paulo, Brazil. We seek to present and analyze the experience of formulating and implementing HIDS, in view of its history of constitution, participating actors, structuring process, and its perspective of the concepts of sustainability and scientific and technological development. The HIDS concerns a partnership between 14 institutions, which correspond to legal categories such as public companies, higher education institutions, state authorities, social organizations, private law foundations, research, development and innovation institutions, multinationals companies, among others. In addition, it aims to contribute to the process of sustainable development, considering the production of knowledge and technologies through national and international cooperation, to mitigate and solve problem-situations in contemporary society. Methodologically, this article consists of bibliographic reviews and access to documents and information published on the institutional website of the researched experience. Considering that HIDS is a project still in the structuring and implementation phase, the focus of the analysis is on presenting the initiative’s formulation trajectory, its context and constitution process, as well as its alignment in relation to the main  mobilized topics. In addition, it is worth discussing which models of international experiences are cited in their constitution process and how these experiences impact the emergence and current structure of HIDS. Therefore, we aim to contribute to the reflection on innovative institutional initiatives, whose main mission is oriented to the promotion of transformative technologies and enterprises, integrated urban development, and sustainability.